Enhanced PCM Solidification in triplex-tube thermal energy storage with optimized configuration of branched-angled fins and Hybrid Nanofluid Integration - Mehdi Mahboobtosi; Ali Gholami; DD Ganji (Results in Engineering)
This study aims to optimize the performance of latent thermal energy storage systems (LTESSs) using phase change materials (PCMs) by integrating hybrid nanoparticles (MoS₂–Fe₃O₄) and an innovative branched-angled fin design in a triplex-tube configuration. A computational model, developed using the Finite Element Method (FEM) and validated by experimental data, was employed to explore the impact of different fin geometries and radiation intensities on PCM solidification. Key Findings include significant improvements in solidification efficiency, thermal response time, and energy performance. The optimization of fin geometry (heights and inclination angles) and thermal radiation led to a 21.94% decrease in solidification time compared to the baseline configuration, alongside a 0.36% drop in average temperature. Additionally, the inclusion of thermal radiation resulted in a 51% improvement in solidification performance, demonstrating deeper thermal penetration and faster phase transformation. Key Findings also highlight a 0.63% reduction in energy consumption, attributed to the enhanced heat transfer facilitated by optimized fin dimensions and orientations. The study underscores the importance of combining geometric and radiative parameters for optimal TES system performance, enabling faster thermal responses and improving energy efficiency, critical for sustainable thermal management in energy systems and industrial applications.